iPad application development for breathing sensor - Lin, Huining. (2013)
This report presents the design of a Graphical User Interface (GUI) App that will display the information received from the fiber optic sensor via Bluetooth 4.0 technology. The deliverable of this project is a Graphical User Interface (GUI) for a mobile device (iPad3) that displays information recorded by the sensors wirelessly. Its main purpose is to provide a non-pharmacologic treatment to resistive hypertensive patients by means of an animation to guide user to slow down their breathing rate. The Application will be used by the A*Star team for demonstrating of the fiber optic sensor’s functionality and application to companies.